2021
DOI: 10.21608/jpp.2021.84334.1043
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Wheat Stress Tolerant Genotypes Among Some Bread Wheat Accessions Using Different Drought Tolerance Indices تحديد الطرز الوراثية المقاومة للإجهاد في بعض تراکيب قمح الخبز باستخدام مؤشرات تحمل الجفاف المختلفة

Abstract: Thirty-nine genotypes of bread wheat (Triticum aestivum L.) collected from different regions in Egypt and two commercial varieties were used in this study, to estimate the tolerance indices and to establish the drought tolerance in 41 genotypes. Significant genotypes mean squares were detected for all studied traits, except number of spikes per m 2 and grain per spike under water stress. Using stress susceptibility index (SSI), genotypes 4, 6, 1, 31, 19, and 24 were classified as highly drought tolerant. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…Furthermore, the presence of significant differences between genotypes would suggest the presence of genotypic variance, which indicates the wide diversity between genotypes and water conditions. ese results agree with the study results of Arab et al [43].…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the presence of significant differences between genotypes would suggest the presence of genotypic variance, which indicates the wide diversity between genotypes and water conditions. ese results agree with the study results of Arab et al [43].…”
Section: Resultssupporting
confidence: 93%
“…The mean performance of 25 genotypes showed that the highest yield value was recorded for Giza 168 followed by Giza 171 under normal irrigation and water stress respectively. The results are similar to those obtained by Abdi et al, (2013) and Arab et al, (2021).…”
Section: Agronomic Physiological Traits and Yield Componentssupporting
confidence: 91%
“…For MP, a significant correlation coefficient for STI was found to be (**0.94). These results are consistent with the findings of Naghavi et al, (2013), also, these findings are in consistence with the findings of Golabadi et al, (2006), Hooshmandi (2018) and Arab et al, (2021) in wheat. Data analysis of correlation coefficients between drought tolerance indices could be a good phenomenon for selection of genotypes having high stress tolerance by using the best selection indices.…”
supporting
confidence: 93%
“…Therefore, selection based on STI might lead to high-yielding tolerant genotypesMenezes et al (2014),(Abdelghany et. al (2016), Abd El-Kreem et al(2019).,Manal and Samah (2019) andArab et al (2021) reported a high STI rate for the genotype presents its high drought tolerance and its high yield Mevlut and Sait (2011). considered that, the genotypes with high STI have difference in yield under stress and non-stress environment that may be revealed small or minor yield reductions under drought condition.…”
mentioning
confidence: 98%